Estimation of Joint Income-Wealth Poverty: A Sensitivity Analysis - Sarah Kuypers; Ive Marx (Institute for the Study of Labor (IZA), 2016)
Most poverty studies build on measures that take account of recurring incomes from sources such as labour or social transfers. However, other financial resources such as savings and assets also affect living standards, often in very significant ways. Previous studies that have sought to incorporate assets into poverty measures suggest that (1) poverty estimates including wealth are considerably lower than income-based measures; (2) poverty rates of the elderly are more affected than those of the nonelderly and (3) poverty rates are especially affected by the household's main residence. This paper assesses the sensitivity of these conclusions to various plausible alternative assumptions, such as the poverty line calculation, the types of assets included in the wealth concept and choices with respect to the equivalence scale. Moreover, we check whether the impact of alternative assumptions is consistent across age and institutional settings. To that effect we compare Belgium and Germany, two countries with similar living standards and income poverty rates, but very different levels and distributions of wealth. Using data from the HFCS we show that accounting for wealth affects the incidence and age structure of poverty in a very substantial way. Country comparisons are also affected in very substantial ways.
Keywords: I32; 330; income; wealth; poverty measurement; sensitivity analysis